Plato and the Ideas: A Very Complicated Story - Lanoue, André,; Migliori, Maurizio,; Fermani, Arianna, (Brill's Plato Studies Series ;, 2025)
This collective volume, at the cutting edge of research, presents a wide range of perspectives on Plato's theory of Ideas. It features numerous authors whose main language of publication is not English, thus providing international readers access to a wide range of scholarly works not normally available to them. In this collective volume, to which a number of established scholars of international renown as well as young up-and-coming researchers have contributed, the Platonic theory of Ideas is examined from philological, historical, psychological, metaphysical and ethical viewpoints, presenting a boldly innovative hermeneutical impulse that meets the highest standards of contemporary research.